Measurement of clinical delay intervals among younger adults with colorectal cancer using health administrative data: a population-based analysis. Issue 1 (21st November 2022) - Castelo, Matthew; Paszat, Lawrence; Hansen, Bettina E; Scheer, Adena S; Faught, Neil; Nguyen, Lena; Baxter, Nancy N
Abstract : Background: Clinical delays may be important contributors to outcomes among younger adults (<50 years) with colorectal cancer (CRC). We aimed to describe delay intervals for younger adults with CRC using health administrative data to understand drivers of delay in this population. Methods: This was a population-based study of adults <50 diagnosed with CRC in Ontario, Canada from 2003 to 2018. Using administrative code-based algorithms (including billing codes), we identified four time points along the pathway to treatment—first presentation with a CRC-related symptom, first investigation, diagnosis date and treatment start. Intervals between these time points were calculated. Multivariable quantile regression was performed to explore associations between patient and disease factors with the median length of each interval. Results: 6853 patients aged 15–49 were diagnosed with CRC and met the inclusion criteria. Males comprised 52% of the cohort, the median age was 45 years (IQR 40–47), and 25% had stage IV disease. The median time from presentation to treatment start (overall interval) was 109 days (IQR 55–218). Time between presentation and first investigation was short (median 5 days), as was time between diagnosis and treatment start (median 23 days). The greatest component of delay occurred between first investigation and diagnosis (median 78 days). Women, patients with distal tumours, and patients with earlier stage disease had significantly longer overall intervals. Conclusions: Some younger CRC patients experience prolonged times from presentation to treatment, and time between first investigation to diagnosis was an important contributor. Access to endoscopy may be a target for intervention.